F FAKTOR FAKTOR YANG MEMPENGARUHI KEPATUHAN KUNJUNGAN LANSIA KE POSYANDU LANSIA DI DESA RANTAU PANJANG HULU KECAMATAN KUSAN HILIR KABUPATEN TANAH BUMBU TAHUN 2020 - Putra, Farhandika; Hikmah, Indah Nurul (Journal of Nursing Invention, 2023)
Background: Posyandu of Elderly is an integrated service post for elderly people in certain agreed areas, which is driven by the community to get health services. Objective: The aim of this study was to determine the factors that influence the obedience of elderly visits to elderly posyandu. Method: This type of stdudy was an analytical survey with a cross sectional approach. The sample in this study were 32 elderly who were registered in the elderly posyandu with total sampling technique. The instruments were used questionnaires and KMS. Result: From the results of the study, it was indicated that the independent variables that had an influence on the obedience of elderly visits were the level of education for elderly (p value = 0.000), the level of knowledge of the elderly (p value = 0.08), attitudes of the elderly (p value = 0.08), socio economic (p value = 0,000), the most influential independent variables were education and socio economic factors with (p value = 0,000). Conclusion: The conclusion from this study, that there were factors that most influence the obedience of elderly visits to elderly posyandu, namely educational and socio-economic factors. Suggestions from this research were expected to cadres and health workers to improve the quality of service by providing counseling for the elderly and their families about the importance of posyandu for elderly